Gender and geographical differences in Australian job-to-job mobility - Diego, Machillanda Flechas (My University, 2023)
This paper investigates gender and geographical differences in the factors associated with job-to-job mobility for the average Australian worker. Using a Generalised Estimating Equations approach and waves 11 to 21 of the Household, Income and Labour Dynamics in Australia (HILDA) survey, I estimate marginal models for workers’ probability of voluntary employer change, promotion, occupation change, and industry change. I find several but disparate gender differences, including in the effect associated with immigration from a nonEnglish speaking background, postgraduate education, and employment in genderconcentrated industries. I also find that household characteristics have limited associations with job-to-job mobility in general and that there are few geographical differences in the factors associated with mobility. These findings highlight the individual characteristics through which group differences in job-to-job mobility do and do not manifest, identifying areas for further research to understand the underlying causal mechanisms and inform targeted policy opportunities.
Keywords: Disadvantage, adversity and resilience; Families and relationships; Gender; Labour market; Learning, education and training